The Effect of Tax Fairness Perception, Tax Knowledge, and Tax Ease on Taxpayer Compliance with Religiosity Attitude as a Moderating Variable: A Case Study of MSME Taxpayers in Tegal City - Rizki, Amelia ana; Indriasih, Dewi; Mubarok, Abdulloh (Jurnal Sains Sosio Humaniora, 2026)
Indonesia's tax revenue depends heavily on the compliance of Micro, Small, and Medium Enterprises (MSMEs), yet the growth of MSMEs in Tegal City has not been matched by a stable rate of tax reporting compliance. This study examines the effect of tax fairness perception, tax knowledge, and tax ease on MSME taxpayer compliance, and tests whether religiosity attitude moderates these relationships. A quantitative approach was applied to 400 MSME taxpayers registered at KPP Pratama Tegal, selected through purposive sampling using the Slovin formula. Data were collected through structured questionnaires and analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with IBM SPSS Statistics 22. The results show that tax fairness perception, tax knowledge, and tax ease each have a significant positive effect on taxpayer compliance, jointly explaining 36.5 percent of its variance. However, religiosity attitude does not significantly moderate any of the three relationships, indicating that the moderated model's explanatory power only marginally increases to 39.8 percent and that the interaction terms remain statistically insignificant. These findings suggest that structural and cognitive factors, namely fairness, knowledge, and administrative ease, are more decisive in shaping MSME tax compliance than internalized religious values. The study recommends that tax authorities continue to simplify administrative procedures and strengthen taxpayer education rather than relying on religiosity-based appeals to improve compliance.